2013
DOI: 10.3390/molecules181013061
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones and Their Derivatives Inhibit High Glucose-Induced NF-κB Activation and MCP-1 and TGF-β1 Expression in Rat Mesangial Cells

Abstract: Diabetic nephropathy (DN) is one of the most common and serious chronic complications of diabetes mellitus, however, no efficient clinical drugs exist for the treatment of DN. We selected and synthesized several sesquiterpene lactones (SLs), and then used the MTT assay to detect rat mesangial cells (MCs) proliferation, ELISA to measure the expression level of monocyte chemoattractant protein-1 (MCP-1), transforming growth factor beta (TGF-β1) and fibronectin(FN), real-time fluorescent quantitative PCR analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…In diabetic nephropathy, high glucose can activate NF-κB and promote the infiltration of inflammatory cells into renal interstitium, leading to ECM accumulation and renal interstitial fibrosis. 26,27 Moreover, the NF-κB superfamily of transcription factors plays an important role in the regulation of renal fibrosis. 28 We found the JSH-23 treatment of HE4-transfected HK2 cells effectively abolished HE4-inhibited MMP2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic nephropathy, high glucose can activate NF-κB and promote the infiltration of inflammatory cells into renal interstitium, leading to ECM accumulation and renal interstitial fibrosis. 26,27 Moreover, the NF-κB superfamily of transcription factors plays an important role in the regulation of renal fibrosis. 28 We found the JSH-23 treatment of HE4-transfected HK2 cells effectively abolished HE4-inhibited MMP2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that SLs, including PTL, micheliolide (MCL), and several synthetic analogs of these molecules, could effectively attenuate the high glucose-stimulated and AOPP-induced activation of NF- κ B, the degradation of I κ B α , and the expression of MCP-1 in rat mesangial cells (MCs) [ 30 , 31 ]. These findings showed that SLs can exert a beneficial role in high glucose-stimulated and AOPPs-induced inflammation and ECM deposition by preventing NF- κ B activation in MCs.…”
Section: Introductionmentioning
confidence: 99%
“…It is speculated that HMGB1-NF-κB may function as a signaling pathway in renal diseases. Previous studies revealed that TGF-β1 was regulated by NF-κB in certain signaling pathways, which indicates a potential role for NF-κB (45,46). Therefore, the present study aimed to investigate the association between HMGB1, NF-κB, TGF-β1 and CAN.…”
Section: Discussionmentioning
confidence: 93%